Development of Low-fat Ice cream Product from Broken Riceberry Rice Using Fat Substitutes - Khongsit, Phensiri; Pancharoen, Suworanee (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research aims to develop a low-fat ice cream product from broken riceberry rice by using fat substitutes. The study investigated the appropriate concentration of riceberry rice slurry at 10 %, 20 %, and 30 % (replacing the water component) in the basic riceberry broken rice ice cream formulation. The results showed that a suitable concentration of riceberry rice slurry was 20 %, replacing the water. The study of types and concentrations of fat substitutes for the low-fat ice cream product included Tween 80 (TW), whey protein isolate (WPI), and maltodextrin (MD) at 2 %, 3 %, and 4 %. It was found that ice cream with MD 4 % had the lowest melt rate and the lowest fat content (p 0.05), with a fat reduction of 85.19 % compared to the basic formulation. Ice cream with TW 4 % had the highest hardness and viscosity (p 0.05), and ice creams with WPI 4 %, MD 3 %, and MD 4 % had the lowest overrun values (p 0.05). Sensory testing with 30 consumers aged 15 - 60 revealed that consumers rated their liking for the color, aroma, taste, and overall acceptability of ice creams with WPI 4 %, MD 3 %, and MD 4 % at a moderate level (scoring between 7.22 and 7.61). The study concluded that the appropriate fat substitute for low-fat broken riceberry rice ice cream is 4% maltodextrin (replacing the coconut milk component). The developed low-fat riceberry broken rice ice cream formula includes the following ingredients: coconut milk, maltodextrin, water, riceberry rice slurry, pandan leaf juice, sugar, and salt, at 38.4, 1.6, 28.0, 7.0, 5.0, 19.7, and 0.3%, respectively.